Immunohistochemical detection of piscine reovirus (PRV) in hearts of Atlantic salmon coincide with the course of heart and skeletal muscle inflammation (HSMI) - Finstad Øystein; Falk Knut; Løvoll Marie; Evensen Øystein; Rimstad Espen (Veterinary Research, 2012)
Abstract Aquaculture is the fastest growing food production sector in the world. However, the increased production has been accompanied by the emergence of infectious diseases. Heart and skeletal muscle inflammation (HSMI) is one example of an emerging disease in farmed Atlantic salmon (Salmo salar L). Since the first recognition as a disease entity in 1999 it has become a widespread and economically important disease in Norway. The disease was recently found to be associated with infection with a novel reovirus, piscine reovirus (PRV). The load of PRV, examined by RT-qPCR, correlated with severity of HSMI in naturally and experimentally infected salmon. The disease is characterized by epi-, endo- and myocarditis, myocardial necrosis, myositis and necrosis of the red skeletal muscle. The aim of this study was to investigate the presence of PRV antigens in heart tissue of Atlantic salmon and monitor the virus distribution in the heart during the disease development. This included target cell specificity, viral load and tissue location during an HSMI outbreak. Rabbit polyclonal antisera were raised against putative PRV capsid proteins μ1C and σ1 and used in immunohistochemical analysis of archived salmon heart tissue from an experimental infection. The results are consistent with the histopathological changes of HSMI and showed a sequential staining pattern with PRV antigens initially present in leukocyte-like cells and subsequently in cardiomyocytes in the heart ventricle. Our results confirm the association between PRV and HSMI, and strengthen the hypothesis of PRV being the causative agent of HSMI. Immunohistochemical detection of PRV antigens will be beneficial for the understanding of the pathogenesis of HSMI as well as for diagnostic purposes.